PENGARUH PENAMBAHAN KOAGULAN BIJI KELOR TERHADAP PENURUNAN KADAR LOGAM KROMIUM (Cr), MANGAN (Mn), DAN TIMBAL (Pb) MENGGUNAKAN ICP-OES (THE ADDITION EFFECT OF KELOR SEEDS COAGULANT ON THE DECREASING OF CHROMIUM (Cr), MANGANESE (Mn), AND LEAD (Pb) LEVELS USING ICP-OES) - Susvira, Dian; Ramadhan, Muhammad Bagus; Susparini, Ninik Triayu; Situmeang, Boima; Widiyanto, Holisha; Bialangi, Nurhayati; Musa, Weny JA (Indonesian Journal of Pure and Applied Chemistry, 2024)
Electroplating process has a negative effect in form metal ions waste. Today, industrial wastewater treatment widely using aluminum sulfate or alum as synthetic coagulants, although hazardous and expensive. This study was conducted to discover the activity of Moringa seeds (Moringa oleifera) as natural coagulants to substitute synthetic coagulants. Trapped metal ions detected by ICP-OES. The results showed that moringa seed coagulants could reduce 53% Cr, 64.56% Mn, and 92.89% Pb in the addition of 15 grams of moringa seed coagulants.